Methane Emissions in a Chemistry‐Climate Model: Feedbacks and Climate Response. (14th October 2020) - Heimann, I.; Griffiths, P. T.; Warwick, N. J.; Abraham, N. L.; Archibald, A. T.; Pyle, J. A.
Abstract: Understanding the past, present, and future evolution of methane remains a grand challenge. Here we have used a hierarchy of models, ranging from simple box models to a chemistry‐climate model (CCM), UM‐UKCA, to assess the contemporary and possible future atmospheric methane burden. We assess two emission data sets for the year 2000 deployed in UM‐UKCA against key observational constraints. We explore the impact of the treatment of model boundary conditions for methane and show that, depending on other factors, such as CO emissions, satisfactory agreement may be obtained with either of the CH4 emission data sets, highlighting the difficulty in unambiguous choice of model emissions in a coupled chemistry model with strong feedbacks. The feedbacks in the CH4 ‐CO‐OH system, and their uncertainties, play a critical role in the projection of possible futures. In a future driven by large increases in greenhouse gas forcing, increases in tropospheric temperature drive, an increase in water vapor, and, hence, [OH]. In the absence of methane emission changes this leads to a significant decrease in methane compared to the year 2000. However, adding a projected increase in methane emissions from the RCP8.5 scenario leads to a large increase in methane abundance. This is modified by changes to CO and NO x emissions. Clearly, future levels of methane are uncertain and depend critically on climate change and on the future emission pathways of methane and ozone precursors. We highlight that further work is needed to understand the coupled CH4 ‐CO‐OH system in order to understand better future methane evolution. Plain Language Summary: Methane is an important greenhouse gas and needs to be modeled accurately to understand climate change. We use a combination of modeling approaches to investigate how we could model methane in present day conditions and in the future. We used a simple box model to explore how methane behaves in the atmosphere and interacts with other important species such as OH and CO. We then used a more complex 3‐D model of the whole atmosphere employing a more physically realistic way to treat methane emissions in our model than is normally done. We show that the choice of emissions data set is difficult but that good agreement with observations is possible. The simple model shows how some of the difficulty arises: The different components of the system interact nonlinearly. We go on to use this 3‐D modeling approach to study methane levels in future climate. We show that not only methane emissions but also other factors are important to methane levels, again agreeing with the broad conclusions of our simple model. Methane in the future is highly uncertain and depends on climate, emissions, and the interactions between them, mediated by key chemical species, CO, methane, and OH. Key Points: We study methane in present and future climate in a model employing flux‐based treatment of methane emissions We examine the source and importance of feedbacks in the CH4 ‐CO‐OH system using a 0‐D box model and a 3‐D chemistry‐climate model We examine methane levels in future climate and the role played by climate and emissions changes